Peradilan Desa Adat sebagai Instrument Integral Pembangunan Hukum Nasional Ditinjau dari Undang-Undang No 6 2014 Tentang Desa - Nurdhin Baroroh (UIN Sunan Kalijaga Yogyakarta, 2015)
This article is based on research about representation of customary judicialpractice and customary law after Law No. 6/2014 About the Village. TheElimination of customary law from the national legal system was not able to remove thewhole customary judicial practice and customary law in social life. Customary justice isstill alive in the daily lives of indigenous peoples. This produces a gap between the legalrealities with reality arbitrate indigenous peoples. Law No. 6/2014 About theVillage will create a lot of consequences at the level of village government in the reestablishment of justice among indigenous villages. Article 103 paragraph “e” mentionsthat one of the responsibilities Customary Village is organizing the peace court assemblyIndigenous Village according to the provisions of laws and regulations. This is a freshwind to the development of village justice. The Article 18 B subsection (2) and Article28 subsection (3) in 1945 Constitution became evidence of the recognition and respectfor the rights of traditional customary law community unit should be derived in thelegislation under the 1945 Constitution. In accordance with the theory of the hierarchyof norms, so every rules or legislation should not contrary with the Basic Constitution,in this case is the 1945 Constitution. With the recognition of traditional rights oftraditional law community unit (including the prosecuting authority) in 1945Constitution, should the existence of customary justice also received recognition in thelaw.